Greenpeace Effort in Opposing Food Estate Development in Indonesia - Yasin, Mevlana; Rokhaniyah, Hesti; Amalia, Novi Rizka; Putra, Alde Mulia (UNIDA GONTOR, 2024)
This research aims to analyze the efforts made by Greenpeace in opposing food estate development. The method used in this research is qualitative method. This research uses a literature study approach. The data used in this research were obtained through scientific journals, theses, related articles, official websites, and documentation from related institutions. The data analysis technique used in this research uses data reduction techniques, the conceptual framework that author uses in this research is the concept of Environmental Non-Governmental Organization and the concept of non-violence. The results of this study show that in an effort to oppose the development of food estate in Indonesia, Greenpeace made efforts described by McCormick in the concept of environmental NGO. The efforts made by Greenpeace in opposing the development of food estates in indonesia are, collaboration with authorized local officials, conducting campaigns, utilizing the media as a means of disseminating campaigns, conducting research, and building public awareness of the importance of maintaining environmental awareness. In addition, Greenpeace also uses a non-violent approach in its actions. This approach is carried out through two methods, protest and persuasion methods.